Identifying Sn Site Heterogeneities Prevalent Among Sn‐Beta Zeolites. Issue 12 (9th November 2016) - Wolf, Patrick; Liao, Wei‐Chih; Ong, Ta‐Chung; Valla, Maxence; Harris, James W.; Gounder, Rajamani; van der Graaff, William N. P.; Pidko, Evgeny A.; Hensen, Emiel J. M.; Ferrini, Paola; Dijkmans, Jan; Sels, Bert; et al.
Abstract : In recent years, various protocols on preparing Lewis acidic Sn‐ β zeolite hydrothermally and postsynthetically have been reported. However, very little is known about the effects of different synthesis protocols on the Sn(IV) speciation in the final material. Even the effects of individual synthesis parameters within a certain preparation method have not been studied systematically. Here, we demonstrate that hydrothermally synthesized Sn‐ β zeolites prepared via very similar recipes show significantly different 119 Sn‐NMR spectra, suggesting different Sn site speciation. Among postsynthetically prepared Sn‐ β zeolites, less variation in the resulting 119 Sn‐NMR spectra have been observed, indicating a more reproducible synthesis procedure compared to hydrothermal synthesis in fluoride media. This work highlights the importance of 119 Sn‐NMR measurements to elucidate the precise local geometry of the Sn heteroatoms in Sn‐ β, and the need to quantify the number of reactive Sn sites on each sample that participate in a given catalytic reaction, in order to accurately compare materials prepared by different routes. Abstract :